2020
DOI: 10.1213/ane.0000000000005266
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Pregnant and Postpartum Extracorporeal Membrane Oxygenation Patients

Abstract: BACKGROUND: The use of extracorporeal membrane oxygenation (ECMO) as a rescue therapy for cardiopulmonary failure is expanding in critical care medicine. In this case series, we describe the clinical outcomes of 21 consecutive pregnant or postpartum patients that required venovenous (VV) or venoarterial (VA) ECMO. Our objective was to characterize maternal and fetal survival in peripartum ECMO and better understand ECMO-related complications that occur in this unique patient population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
2
35
2
1
Order By: Relevance
“…Upon further analysis of laboratory tests in Table 3 , it appears that liver enzyme indicators were more sensitive and potentially showed damage from ECMO initiation, whereas renal function indicators remained largely normal due to favorable basic renal function. Similar to other clinical studies ( 17 – 19 ), our data suggest that early application of ECMO obviously improves patient perfusion and leads to more favorable outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Upon further analysis of laboratory tests in Table 3 , it appears that liver enzyme indicators were more sensitive and potentially showed damage from ECMO initiation, whereas renal function indicators remained largely normal due to favorable basic renal function. Similar to other clinical studies ( 17 – 19 ), our data suggest that early application of ECMO obviously improves patient perfusion and leads to more favorable outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Continuation of pregnancy is only recommended for fetuses that will survive with a follow-up short-term pregnancy. Mazzeffi et al suggested that general obstetric indications should be retained, but more studies are expected ( 17 ). There are some limitations in our study; for example, the etiologies of cases are relatively scattered and the cases are low in number.…”
Section: Discussionmentioning
confidence: 99%
“… 87 Extracorporeal membrane oxygenation has been shown in small studies to be an effective rescue therapy in pregnant and postpartum mothers. 88 , 89 Cardiac transplantation is only pursued when mechanical circulatory support is not feasible or desired, or for patients who fail to recover 6 to 12 months after onset. 68 …”
Section: Therapeutics and Principles Of Managementmentioning
confidence: 99%
“…The level of evidence for the use of ECMO among pregnant women is very low. ECMO has been mostly used to treat refractory hypoxemia in pregnant women with adult respiratory distress syndrome (ARDS), with a veno-venous circuit [37][38][39], and PE remains a marginal indication (5% of all cases). When considering all indications of VA-ECMO, the reported cases had a high 30-day maternal survival (72.4%), which was similar for the subgroup of patients with PE (11/17, 64.7%) [40].…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%
“…There is no consensus on the appropriate obstetrical monitoring in pregnant women on ECMO. Some propose a continuous CTG for the first 24 h after ECMO initiation, and twice daily thereafter in case of hemodynamic stability [46].…”
Section: Extracorporeal Membrane Oxygenation (Ecmo)mentioning
confidence: 99%